PEMANFAATAN HUTAN OLEH SUKU KAMORO DI KAMPUNG TAPORMAY DAN AINDUA DISTRIK MIMIKA BARAT-JAUH KABUPATEN MIMIKA PROVINSI PAPUA - M.J. Sadsoeitoeboen (FMIPA Universitas Papua, 2014)
A study has been conducted in the lowland of tropical rain forest, swamps and mangroves in the vicinity of Tapormay and Aindua villages in the Far-West Mimika District from Mimika Regency, Papua Province to examine the diversity of plant and animal species and the number of plant and animal species utilized by the Kamoro tribe in the villages in they everyday life. A descriptive method with survey technique and interview to the people in Tapormay and Aindua villages were used to carry out the study. The results of the study found 36 dominant plants species in lowland tropical rain forest, five dominant species in swamp forest and nine dominant plant species in mangrove forest. While as many of 35 wildlife species were encountered in lowland tropical rain forest, marshes and mangroves consisting of nine species of mammals/marsupials, 24 species of birds and two species of reptiles. Non-timber forest products recorded by the Kamoro in both villages were 47 species divided into 10 groups: food and beverages, household necessities, sleeping equipment and rain hood, hunting tools, medicines, oil, sources of firewood, tribe ornaments, wooden boats, and musical instruments. Based on the level of forest importance or the most important function of forest area for the Kamoro is as a place to find food, that is: sago and hunting. Interview with all respondents (100%) stated that the main function of the forest is where to take sago followed by hunting activities, picking up firewood, wooden boats, fruits and medicines, and taking building materials and bark.